From Ecological Crisis to Utopian Hope: Kim Stanley Robinson's Science in the Capital Trilogy as Realist Critical Dystopia. Issue 2 (2015) - King, Derrick
Abstract : This essay explores the utopian political possibilities of the ecological disaster novel through a reading of Kim Stanley Robinson's Science in the Capital trilogy (2005-2007). Robinson's trilogy offers a crucial intervention into visions of ecological catastrophe by formally negotiating between the conceptual categories of "disaster, " "crisis, " and "event" in a way that leaves liberal reformist solutions untenable while at the same time refusing ahistorical and anti-dialectical fantasies in which disaster becomes the magical solution that will automatically create change. This essay claims that the cultural form it names the "realist critical dystopia" best captures this utopian dynamic.